Poor Jack - Marryat, Frederick, 1792-1848 (Salt Lake City, UT : Project Gutenberg, 2007)
"Poor Jack" by Captain Frederick Marryat is a novel written in the early 19th century. The story is largely set in the realm of the River Thames in London and revolves around the life of Jack Saunders, exploring themes of social status, family dynamics, and personal struggles of various characters. Through its vivid narrative, the book promises an engaging blend of adventure and social commentary reflective of its time. The opening of "Poor Jack" introduces readers to the protagonist's ancestry, particularly focusing on Jack's father, who served as a captain's coxswain. The narrative unfolds with a humorous and critical reflection on Jack's family origins, especially highlighting the not-so-glamorous mother, Araminta, who exhibits pride and confrontations due to her past as a ladies' maid. As the initial chapters detail the intricacies of family relationships marked by disdain and a struggle for dignity, readers are drawn into Jack's evolving circumstances, setting the stage for his adventures and personal growth as he navigates the complexities of life by the Thames. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Poor_Jack
There is an improved edition of this title, eBook #14222
Release date is 2007-05-22
Produced by Nick Hodson of London, England
Keywords: Sea stories; Poor -- Fiction